Natural born monads : on the metaphysics of organisms and human individuals - Altobrando, Andrea; Biasetti, Pierfrancesco (Berlin : De Gruyter, 2020)
In this book, the authors explore a distinct intellectual trajectory that begins with Leibniz's concept of the monad in the 17th century, continues through the works of Kant and Hegel, and ultimately reaches Japan$1 (Bthe first Eastern country to engage with and challenge Western philosophy and sciences. This line of thought has since evolved into one of the central voices in contemporary debates within the philosophy of biology, philosophical anthropology, and social philosophy. The volume offers both a historical and systematic examination of a particular perspective on individuals and their environments, seeking to integrate their natural context with their dialectical nature. This historical and systematic approach provides a framework for assessing how the life sciences shape our understanding of individual lives, human activities, institutions, politics, and, ultimately, humanity as a whole.s
Includes index.
Keywords: monad; individual; human nature; Organism